Assessment of food addiction using the Yale Food Addiction Scale 2.0 in individuals with binge-eating disorder symptomatology: Factor structure, psychometric properties, and clinical significance. (September 2019) - Linardon, Jake; Messer, Mariel
Highlights: Tested the factor structure and psychometric properties of the YFAS 2.0 in those with binge-eating disorder symptomatology. A unidimensional structure was upheld, and the psychometric properties were confirmed. Food addiction predicted unique variance in impairment, highlighting the clinical significance of this construct in BED. There is a potential need to screen and assess addictive-like eating behaviours during interventions for BED. Abstract: The Yale Food Addiction Scale 2.0 (YFAS) assesses addiction-like eating of palatable foods based on the 11 diagnostic criteria for substance use disorder in the Diagnostic and Statistical Manual of Mental Disorders (DSM-5). This study was the first to investigate the factor structure, psychometric properties, and clinical significance of the YFAS 2.0 in individuals with binge-eating disorder (BED) symptomatology. Data were analysed from 220 community-based participants who met criteria for "probable BED" based on self-report symptom frequency. Classification of food addiction (FA) was met by 42.3% of the sample. The YFAS 2.0 exhibited a unidimensional structure, adequate internal consistency, and convergent and incremental validity. YFAS 2.0 scores contributed the largest percentage of unique variance in psychological distress and impairment over other BED features (overvaluation of weight and shape, binge eating, BMI), highlighting the clinical significance of the FA construct in BED. Support for the validity and reliability of the YFAS 2.0 in individuals with BED-like symptoms was found. Findings also suggest that the presence of FA may represent a more disturbed group of BED characterised by greater general and eating disorder-specific psychopathology. Our findings overall highlight the potential need to screen and assess addictive-like eating behaviours during interventions for BED.